Understanding and Controlling Molecular Compositions and Properties in Mixed-Linker Porphyrin Metal-Organic Frameworks - Senge, Mathias (My University, 2024)
Porphyrin-based metal-organic frameworks (MOFs) are attractive materials for photo- and thermally activated catalysis due to their unique structural features related to the porphyrin moiety, guest accessible porosity and high chemical tunability. In this study, we present a synthetic approach for the integration of nonplanar β-ethyl-functionalized porphyrin linkers into the framework structure of PCN-222, resulting in a solid solution series of materials with different functionalized linker contents. Comprehensive analysis by a combination of characterization techniques such as NMR, UV-vis and IR spectroscopy, powder X-ray diffraction and N2 sorption analysis allows for the confirmation of linker incorporation. A detailed structural analysis of intrinsic material properties such as the thermal response of the different materials underlines the complexity of synthesizing and understanding such materials. This study presents a blueprint for synthesizing and analyzing porphyrin-based mixed-linker MOF systems and highlights the hurdles of characterizing such materials.